Fin Erosion of Salmo salar (Linnaeus 1758) Infested with the Parasite Caligus rogercresseyi (Boxshall & Bravo 2000) - Margarita P. González; Sandra L. Marín; Melinka Mancilla; Hernán Cañon-Jones; Luis Vargas-Chacoff (Animals, 2020)
Fin condition is a simple indicator of fish welfare, which anticipates detrimental effects on fish in aquaculture systems. This study evaluated the fin condition of Salmo salar at different abundances of the parasite Caligus rogercresseyi. Fish were exposed to infestation with copepodids and the cohort was allowed to develop to the adult stage. The relative fin index was measured. Significant differences between infested and control fish for both pectoral and anal fins were observed. Moreover, there were significant negative relationships between fin condition and parasite abundances for pectoral, anal, and pelvic fins, suggesting that infestations with C. rogercresseyi could be a possible cause for fin damage in Atlantic salmon. Moreover, this damage was associated with increased stress levels, suggesting that damage can be related to physiological changes on infested fish. According to these results, pectoral fin assessments have the potential to provide information on the welfare of fish with C. rogercresseyi infestation. Determining the causes of poor fin development may improve fish welfare, even when infested by parasites.